Production of construction materials in the industrial and economic development - Nurpeisov, B.G.; Bazarbaev, M.K.; Zhakina, G.E.; Bazarbaeva, L.M. (BUKETOV BUSINESS REVIEW, 2017)
In article is considered productions of construction materials in system of Industrial and innovative development in the State program. The article discusses the production of building materials in the system of industrial-innovative development of the State program. The analysis of development of the industry for the production of building materials with an increase in private construction in the framework of public-private partnership. in the «export-import» system is shown exports of building materials in the context of countries. Anoliziruetsya dynamics of export-import operations, identified the main directions of these operations and their geography (country side). The parameters of the index of physical volume, the causes of positive change in the index. The analysis of the GDP has allowed to show the positive dynamics of the share of products stroytelnoy industries and factors this trend. The necessity of state interference in the activities of this industry in the management format directly in the format of the public sector of the production and format to stimulate support for the protection of the private sector, in the format of the creation of conditions to the private sector for the implementation of advanced investment projects. In this situation, given proposals to improve the production of building materials.